Willingness to pay for Solid Waste management in Luang Prabang City, Luang Prabang province - Chounlamany , Latsamy; CHANTHAVONE, Thongphanh; Phounnaly, Phayvanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The purposes of the study were: 1) to investigate the comprehension and opinions of the people and entrepreneurs in solid waste management; 2) to explore the satisfaction and requirements of the people and entrepreneurs on the solid waste management service quality of the Urban Service Office; and 3) to investigate factors affecting willingness to pay for solid waste management in Luang Prabang city. The contingent valuation method was used on 369 people from households and entrepreneurs in the study. Questionnaires were used as a data collection instrument, and statistics used for data analysis are frequency, percentage, mean, and standard deviation. The binary regression to analyze cross-section data for surveys. The results found that: The level of satisfaction of the people and entrepreneurs with the quality of the solid waste management service provided by the Urban Service Office was at a moderate level. Which The moderate satisfaction was found in the tangibles. followed by empathy, responsiveness, assurance, and reliability, respectively. The requirements of the people and entrepreneurs on the solid waste management service quality of the Urban Service Office have many needs compared to the current situation. which include: Garbage collection must be done immediately when there is an emergency involving solid waste, such as at festivals, weddings, 2) The Urban Service Office must have a quick response and waste collection quickly, and garbage collection must be done in an orderly manner so that there is no waste water spilling or garbage falling on the road; 3) Garbage collectors, including service staff, must be polite and neat at the time of coordination. 4) separate bins of waste for four points per village or important place, 5) The urban service office must organize training on how to separate garbage for people and entrepreneurs. 6) a week, pick up trash three times. 7) Garbage collectors increased to four people per vehicle, 8) garbage trucks must be increased to four trucks; 9) improve garbage trucks to avoid pollution; and so on. 85.09% of all respondents are willing to pay for solid waste management in Luang Prabang City at an average price of 27,022.29 kip per month, which is higher than the current price of 20,000 kip. Factors affecting willingness to pay for solid waste management in Luang Prabang city consist of six factors, such as service price, ownership of residential or commercial units, the average amount of solid waste, income, age, and education level.